On the Performance of General Cache Networks - CHOUNGMO FOFACK, Nicaise; DEHGHAN, Mostafa; TOWSLEY, Don; BADOV, Misha; GOECKEL, Dennis L. (EAI Endorsed Transactions on Cloud Systems, 2015)
The performance evaluation of cache networks has gain a huge attention due to content-oriented delivery technologies. If general network topologies are more realistic than hierarchical networks widely studied in the literature, their analysis is significantly challenging. Existing models mainly focus on trees where content custodians are located at the root and the one-way child-to-parent request forwarding schema is common. In this paper, we consider complex and irregular networks where requests may flow possibly in opposite directions from/to several sources/destinations. Moreover, we assume that caches may run one of Time-To-Live (TTL)-based policies recently introduced for content-centric networks and modern Domain Name System [5]. We then derive an analytical framework and a polynomial-time algorithm that approximate accurately performance metrics of arbitrary graph-based and heterogeneous TTL-based cache networks. Simulations show that our simplified methodology may accurately predict metrics of interest on networks of caches running popular replacement algorithms (e.g. LRU, FIFO, or Random) without restricting its scope of application to this interesting use case. Unlike existing approaches, ours scales as network and content catalog sizes increase.